THE EFFECT OF CORPORATE GOVERNANCE MECHANISM, STAKEHOLDER PRESSURE, AND PROFITABILITY ON INTEGRATED REPORTING - Lodovicus Lasdi; Elisabeth Listiyani Oematan (Bina Nusantara University, 2021)
This study aims to examine the effect of corporate governance mechanisms, stakeholder pressure, and profitability on integrated reporting, with firm size as a control variable. The research object used is a manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2017-2020 with purposive sampling method as a sample collection method. The data analysis technique used is multiple linear analysis. The results showed that independent commissioners and firm size had a positive effect on integrated reporting. Meanwhile, the audit committee has a negative effect on integrated reporting. In addition, stakeholder pressure and profitability are not proven to have an effect on integrated reporting.